UPAYA TRANSFORMASI KONFLIK OLEH SEARCH FOR COMMON GROUND ORGANIZATION DALAM KONFLIK DONGO (2010-2013) - Nancy Waas, Anastasia; Fasisaka, Idin; Intan Prameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTRACT The focus of this study is conflict transformation efforts undertaken by Search for Common Ground Organization in Dongo Conflict, Democratic Republic of Congo, from 2010 to 2013. This research is qualitative descriptive interpretive. The result of this  research shows that peace education can be a means to transform the communal conflict in a region. SFCG transform the Dongo conflict by implementing peace education through dialogue, media, and community. These efforts then opened the door for positive peace in Dongo. Keywords: Conflict transformation, peace education, SFCG, Dongo conflict.